Impact of tobacco smoking on the patient's outcome after (chemo)radiotherapy for anal cancer. (December 2020) - Lerman, Jacques; Hennequin, Christophe; Etienney, Isabelle; Abramowitz, Laurent; Goujon, Gael; Gornet, Jean-Marc; Guillerm, Sophie; Aparicio, Thomas; Valverde, Alain; Cattan, Pierre; Quéro, Laurent
Abstract: Purpose: Anal squamous cell carcinoma is associated with multiple risk factors, including infection with human papillomavirus and human immunodeficiency virus, immunosuppression, multiple sex partners, receptive anal sex and tobacco smoking. The aim of our study was to identify prognostic factors associated with poor outcomes after radiotherapy for anal cancer. Methods: We analysed retrospectively the medical records of 171 patients treated by (chemo)radiotherapy for non-metastatic anal cancer in our institution from 2000 to 2015. Patients and tumour characteristics, treatments (chemotherapy, radiotherapy [RT] and surgery) and outcomes were reported. Colostomy-free survival (CRF), disease-free survival and overall survival (OS) at 5 years were studied. Univariate and multivariate analyses were performed by logistic regression to determine factors associated with poor progression-free survival (PFS). Results: Patients' characteristics were as follows: median age, 62 years (range = 36–89); gender, 45 men (26%) and 126 women (74%); HIV serology, positive: 21 patients (12%); tobacco smoking, 86 patients (50%), among whom 28 patients and 58 patients were current and former smokers, respectively. Tumours were classified as locally limited (T1–2, N0, M0) for 86 patients (50%) and locally advanced (T3–4 or N+, M0) for 85 patients (50%). The median total dose was 64.4 Gy (range = 54–76.6), and 146 patients were treated by concurrent chemoradiotherapy. Factors associated with poor PFS in univariate analysis were as follows: tumour size >4 cm, lymph node involvement, tobacco smoking, no initial surgical excision and anal warts at diagnosis. In multivariate analysis, only tobacco smoking status was significantly associated with poor PFS (hazard ratio = 2.85, 95% confidence interval [1.25–6.50], p = 0.013). Five-year PFS for non-smokers, former smokers and current smokers was 88.1%, 76.7% and 73.8%, respectively (p = 0.038). Tobacco smoking was also associated with poor overall survival (p = 0.03), locoregional relapse-free survival (LRFS; p = 0.05) and CFS (p = 0.02). Conclusions: Tobacco smoking status is associated with poor OS, LRFS, PFS and CFS in patients treated for anal cancer by high RT dose ± chemotherapy. Highlights: The patients's smoking status is associated with increased risk for anal cancer recurrence, colostomy and death. The patient's smoking history (current smoker; ex-smoker; never smoker) is also associated with patient's outcome. The patient's smoking status overcomes all prognostic factors in anal cancer treated by radiotherapy.